Recent advances and perspectives on thin electrolytes for high-energy-density solid-state lithium batteries - Yang, Xiaofei; Adair, Keegan R; Gao, Xuejie; Sun, Xueliang (Energy & environmental science, 2021)
Solid-state lithium batteries (SSLBs) are promising next-generation energy storage devices due to their potential for high energy density and improved safety. The properties and physical parameters of the solid-state electrolyte (SSE), as a critical component of the battery, have a significant effect on the electrochemical performance and energy density. In recent years, thick SSEs have been widely used in SSLBs but present several drawbacks in terms of increased internal resistance, additional inactive material content, low practical energy densities, and higher battery manufacturing costs. Reducing the thickness of SSEs and developing high-performance thin SSE-based SSLBs are essential for the commercialization of SSLBs. In this review, we comprehensively summarize the fabrication methods of thin SSEs, their rational design, and their manufacturing processes and applications in different SSLB systems. Moreover, advanced characterization techniques for understanding the Li + transport kinetics and structural evolution of SSEs at the interface are introduced. Additionally, the gravimetric/volumetric energy densities for various SSLB pouch cells with SSEs less than 100 μm thick are evaluated. Lastly, other cell design parameters are tuned to achieve gravimetric/volumetric energy densities over 300 W h kg −1 /500 W h L −1 , and the future directions of thin SSEs in SSLBs are speculated upon. This review summarizes the recent progress of thin solid-state electrolytes for high energy-density solid-state lithium batteries.